Maternal infections during pregnancy and the risk of childhood leukaemia in the offspring: Evidence from large-scale cohort studies - He, J (2021)
Background: Leukaemia is the most common childhood cancer, but its aetiology remains unclear. Maternal infection during pregnancy might lead to chromosomal or immunological alterations in the fetus and could be a risk factor for childhood leukaemia. Clarifying the roles of maternal infections in the development of childhood leukaemia would be helpful for the prevention of this disease.